PENERAPAN METODE ROLE PLAYING PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS V MADRASAH IBTIDAIYAH GUPPI CININI INDRAMAYU - Annisa Kamalia; Abdur Rahim (Bajang Institute, 2022)
The learning process often looks monotonous, many teachers only use classical methods such as lectures and questions and answers, so students tend to be passive during the teaching and learning process. There are many learning methods that can be used by teachers to get around so that students are active when participating in the learning process, besides that the teacher must pay attention to the alignment of the method with the material to be taught. This study aims to determine whether the roleplaying method in learning Indonesian for fifth grade students at Madrasah Ibtidaiyah GUPPI Cinini can be applied, and to find out how the steps of the roleplaying method in learning Indonesian for fifth grade students at Madrasah Ibtidaiyah GUPPI Cinini. The type of research used in this research is descriptive qualitative research. The population of this study were all students of MI GUPPI Cinini, then the sample was fifth grade which collected 21 students. The sample was taken using a purposive sampling technique, namely the technique of determining the sample with certain considerations. Collecting data using observation, interviews, and direct teaching in fifth grade. The results of data analysis show that the application of the role playing method in learning Indonesian in fifth grade MI GUPPI Cinini is said to be successful and can be carried out properly and orderly, this can be seen from the enthusiasm of students when role playing using learning In Indonesian, students can easily understand the rhyme discussion and are enthusiastic in answering the questions given by the researcher and when the researcher asks students to make rhymes, and when writing impressions and messages, some students make them with rhymes.